USM JOINS THE MALAYSIAN YUNUS SOCIAL BUSINESS NETWORK - MPRC, Pusat Media & Perhubungan Awam (2017)
KUALA LUMPUR, 19 February 2017 Universiti Sains Malaysia (USM) has become one of the pioneer members, alongside four other local institutions, in the smart partnership network of the Malaysian Yunus Social Business (MYSB).